A Visualized Analysis of the Research Status and Development Trends of Archaeological Cultural Interaction Since 2000: A CiteSpace-Based Study - Xia Baoguo; Liu Fei (Utan Kayu Publishing, 2026)
Based on bibliometric methods and assisted by CiteSpace and visualization tools, this study systematically reviews and analyzes relevant literature on archaeological cultural interaction over the past two decades. By examining publication trends, institutional collaboration networks, and keyword co-occurrence and burst characteristics, it reveals the developmental trajectory and research features of this field. The results indicate that research on archaeological cultural interaction has shown a continuous growth trend, with a particularly significant increase after 2017. Research institutions are predominantly domestic, with relatively limited international participation. Although several core nodes have formed within collaboration networks, overall connections remain relatively loose. The evolution of research themes demonstrates a progression from early studies on cultural types and distributions, to regional and typological analyses, and further toward methodological integration and in-depth studies of key regions.